2014
DOI: 10.1007/82_2014_394
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infections in Influenza Virus Infection Pathogenesis

Abstract: Influenza is often complicated by bacterial pathogens that colonize the nasopharynx and invade the middle ear and/or lung epithelium. Incidence and pathogenicity of influenza-bacterial coinfections are multifactorial processes that involve various pathogenic virulence factors and host responses with distinct site- and strain-specific differences. Animal models and kinetic models have improved our understanding of how influenza viruses interact with their bacterial co-pathogens and the accompanying immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 169 publications
(269 reference statements)
4
133
1
Order By: Relevance
“…the innate immune cell response, lung inflammatory response, and T cellular response, are also important to the defense against coinfection. Similar to the study of Wolf et al (20) and other reports (8,9,(39)(40)(41), the current study also demonstrated that coinfection significantly increased Ly6G ϩ neutrophils and F480 ϩ macrophages infiltrating the lung (Fig. 7A) and enhanced lung inflammatory cytokine and chemokine levels (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…the innate immune cell response, lung inflammatory response, and T cellular response, are also important to the defense against coinfection. Similar to the study of Wolf et al (20) and other reports (8,9,(39)(40)(41), the current study also demonstrated that coinfection significantly increased Ly6G ϩ neutrophils and F480 ϩ macrophages infiltrating the lung (Fig. 7A) and enhanced lung inflammatory cytokine and chemokine levels (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Prior influenza virus infection has been demonstrated to impair the immune defense against subsequent pneumococcal growth and infection (8,9). For example, influenza virus can desensitize epithelial cells and alveolar macrophages to Toll-like receptor (TLR) signals for defense against bacteria (10).…”
mentioning
confidence: 99%
“…IAV infection is often made more severe by secondary bacterial infection of the upper respiratory tract [72]. While AM should serve as a protection against bacterial co-infection, bacterial clearance is impaired in a model of IAV/S.…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%
“…17 We reasoned that the release of sTREM-1 is at least partly responsible for impaired innate immune responses to bacteria following influenza virus infection. We now report a matrix metalloproteinase (MMP)-9 cleavage site within the TREM-1 sequence and demonstrate an in vivo correlation between MMP-9 expression, the appearance of sTREM-1 in airway lavage and neutrophil recruitment during pulmonary influenza infection.…”
Section: Introductionmentioning
confidence: 99%